A SYSTEMATIC LITERATURE REVIEW ON PRACTICES AND ROLES OF PARENTAL SUPPORT IN FOSTERING LEARNER AUTONOMY IN PRIMARY SCHOOL ENGLISH CLASSROOMS - Punnithann Subramaniam; Amelia Abdullah, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Teachers focus on learner autonomy because it is important, especially in primary English classrooms. While many educators discuss the skills they use, how parents can help students gain autonomy is not often talked about. This systematic literature review (SLR) aims to bring together empirical results on how parents help their children develop autonomy in learning English at primary school. In line with PRISMA 2020, studies published as empirical research in Google Scholar, ERIC and Scopus databases during the years 2015 to 2025 were identified as well as reviewed. Using strict inclusion and exclusion criteria, the researcher chose 32 articles for review. Researcher pulled out the data and organized it using thematic synthesis, focusing on parental practices as well as roles to help children learn independently. Six core practices emerged: (1) homework supervision, (2) provision of learning resources, (3) encouragement, (4) language exposure, (5) creation of a language-rich home environment and (6) parent-teacher communication. As a result of these practices, children can handle their own learning activities and self-regulate while learning English. Five parental roles were discovered: motivator, co-learner, monitor, communicator and emotional supporter. All of these roles contribute to young students being motivated, persistent and reflective. It is clear from the findings that learner autonomy is built from the interactions between school and home environments. Parents should use autonomy-supportive approaches in both daily routines and their emotional interactions with children. The review points out that collaboration between schools and families helps build lifelong learning habits, especially where English is not the first language of children. Recommendations include fostering parental awareness and designing programs to align home support with classroom goals.